The Influence of it Incident Management and Training on Service Improvement: Does Organizational Dehumanization Have an Impact? - Hasbi, Sahlan; Hanafi, Syafiq Mahmadah (International Journal of Economics (IJEC), 2024)
This study aims to identify the positive impact of training and incident management on service recovery performance and the negative impact of organizational dehumanization on service recovery performance. The results showed that training and incident management have a positive effect on service recovery performance. However, the moderation of organizational dehumanization does not have a significant effect on reducing service recovery performance but instead strengthens it. This research provides more understanding that the implementation of banking operations, including Islamic banking, must be carried out with strict regulations, including the affirmation of provisions that can be interpreted as a pattern of organizational dehumanization. However, to strengthen and accelerate the post-incident service recovery process, it must be supported by continuous and quality training.